Dehydrocoupling of phosphine–boranes using the [RhCp*Me(PMe3)(CH2Cl2)][BArF4] precatalyst: stoichiometric and catalytic studies. Issue 3 (12th January 2016) - Hooper, Thomas N.; Weller, Andrew S.; Beattie, Nicholas A.; Macgregor, Stuart A.
Abstract : Detailed experimental and computational studies are reported on the fundamental B–H and P–H bond activation steps involved in the dehydrocoupling/dehydropolymerization of primary and secondary phosphine–boranes, H3 B·PPhR′H (R = Ph, H), using the [RhCp*(PMe3 )Me(ClCH2 Cl)][BAr F 4 ] catalyst. Abstract : We report a detailed, combined experimental and computational study on the fundamental B–H and P–H bond activation steps involved in the dehydrocoupling/dehydropolymerization of primary and secondary phosphine–boranes, H3 B·PPhR′H (R = Ph, H), using [RhCp*(PMe3 )Me(ClCH2 Cl)][BAr F 4 ], to either form polyphosphino-boranes [H2 B·PPhH] n ( M n ∼ 15 000 g mol −1, PDI = 2.2) or the linear diboraphosphine H3 B·PPh2 BH2 ·PPh2 H. A likely polymer-growth pathway of reversible chain transfer step-growth is suggested for H3 B·PPhH2 . Using secondary phosphine–boranes as model substrates a combined synthesis, structural (X-ray crystallography), labelling and computational approach reveals: initial bond activation pathways (B–H activation precedes P–H activation); key intermediates (phosphido-boranes, α-B-agostic base-stabilized boryls); and a catalytic route to the primary diboraphosphine (H3 B·PPhHBH2 ·PPhH2 ). It is also shown that by changing the substituent at phosphorus (Ph or Cy versus t Bu) different final products result (phosphido-borane or base stabilized phosphino-borane respectively). These studies provide detailed insight into the pathways that are operating during dehydropolymerization.